The Subjectivity Of Participation - Nissen, M. author. aut Link
XIII, 292 p.
Keywords: What is a 'we' a collective and how can we use such communal self-knowledge to help people? This book is about collectivity, participation, and subjectivity and about the social theories that may help us understand these matters. It also seeks to learn from the innovative practices and ideas of a community of social/youth workers in Copenhagen between 1987 and 2003, who developed a pedagogy through creating collectives and mobilizing young people as participants. The theoretical and practical traditions are combined in a unique methodology viewing research as a contentious modeling of prototypical practices. Through this dialogue, it develops an original trans-disciplinary critical theory and practice of collective subjectivity for which the ongoing construction and overcoming of common sense, or ideology, is central. It also points to ways of relating discourse with agency, and fertilizing insights from interactionism and ideology theories in a cultural-historical framework.